Survey on Data Leak Detection Algorithms - Thrupthy Mohanan, A; George, Jimy; Nisha, SM; Sainudeen, Lemya (International Journal of Computer Sciences and Engineering, 2025)
The data leak detection plays a major role in organizational industry. The data leak poses serious threat to online social Medias, sensitive datas and so on. We take two papers for this survey. Both of them belong to the area of information forensic and security. In first survey, paper develops a model [PPDLD] the model is based on fuzzy finger print method. The goal of this paper is to generate special type of digest is called fuzzy fingerprint. Rabin finger print algorithm is introduced here just for sampling. A filtering method is used during the digestion process. In second survey, paper deals the fast detection of transformed data leak. This paper suggests a preserving method based on alignment algorithm. The paper aim to detect long and inexact leak patterns from sensitive data and network. Detection is based on comparable sampling algorithm.The data leak detection plays a major role in organizational industry. The data leak poses serious threat to online social Medias, sensitive datas and so on. We take two papers for this survey. Both of them belong to the area of information forensic and security. In first survey, paper develops a model [PPDLD] the model is based on fuzzy finger print method. The goal of this paper is to generate special type of digest is called fuzzy fingerprint. Rabin finger print algorithm is introduced here just for sampling. A filtering method is used during the digestion process. In second survey, paper deals the fast detection of transformed data leak. This paper suggests a preserving method based on alignment algorithm. The paper aim to detect long and inexact leak patterns from sensitive data and network. Detection is based on comparable sampling algorithm.